PENGEMBANGAN BAHAN AJAR DAN MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR MATEMATIKA SISWA - pusfarini pusfarini; Sucipto Sucipto (Universitas Muhammadiyah Lampung, 2019)
The development of teaching materials and learning media used by teachers in providing lessons is expected to help students master basic competencies. The method used in this research is a quantitative descriptive method, data collection is used essay tests. 23 Bandar Lampung. The population is 239 students spread over 6 classes. In the study, two classes were sampled, namely class VII D and VII E, totaling 80 students. Sampling using cluster random sampling technique. Data analysis using the t test formula. From the results of hypothesis testing using the statistical formula t-test, it was obtained thit = 4.71, in the similarity test the two averages for = 0,05 were obtained = 2.00, and For = 0.01 obtained = 2.66. Because thit > tdaf f then the hypothesis Ho is rejected, meaning Ha is accepted. So it can be concluded that